Effect of hemodialysis on high-sensitivity cardiac troponin T levels in patients with hypervolemia - Tinawi, Mohammad; Bastani, Bahar (Frontiers in Nephrology, 2025)
BackgroundHigh-sensitivity cardiac troponin T (hs-cTnT) is widely used in the diagnosis of acute coronary syndrome (ACS) because it is a marker of myocardial damage. Most patients with end-stage kidney disease (ESKD) on renal replacement therapy have elevated plasma hs-cTnT levels at baseline. The impact of hemodialysis (HD) on hs-cTnT levels remains unclear. This study aimed to determine the effect of HD in patients with ESKD and hypervolemia on plasma hs-cTnT levels.MethodsWe conducted a retrospective study of ESKD patients admitted to two community hospitals over a three-year period (from January 1, 2020, to December 31, 2022). All patients had hypervolemia on admission. Plasma hs-cTnT levels were measured at admission and repeated 5.5 ± 0.75 hours after HD. Over the study period, 20 patients with ESKD and hypervolemia fulfilled the inclusion criteria. Two patients were diagnosed with ACS.ResultsPre-HD and post-HD hs-cTnT were elevated in 85% of patients. The data did not follow normal distribution. The median and interquartile range (IRQ) for pre-HD hs-cTnT was 126 (154) ng/L, and for post-HD hs-cTnT was 155 (234) ng/L. Following a single HD session with a high-flux dialyzer, hs-cTnT levels increased in 80% of the cohort, with a mean rise of 25.6% (p = 0.0042). Mean volume removal was 2.4 L, range (1–5 L). Two patients were diagnosed with ACS. Mortality over the study period was 40%, with cardiovascular disease as the leading cause of death.ConclusionIn ESKD patients with hypervolemia, a single HD session using a high-flux dialyzer significantly increased hs-cTnT plasma level. Pre-dialysis hs-cTnT measurements should be used as a clinical baseline when evaluating for ACS, and post-dialysis elevations should be interpreted with caution. Serial measurements may improve diagnostic accuracy. Further prospective studies are needed to clarify the mechanisms and clinical implications of these findings.